REPAIRING GENES, RESTORING STRENGTH: THE PROMISE OF MODERN GENE THERAPY IN DUCHENNE MUSCULAR DYSTROPHY - Katarzyna Kozon; Agnieszka Floriańczyk; Ewa Romanowicz; Aleksandra Kołdyj; Agnieszka Ozdarska; Adrian Krzysztof Biernat; Marcin Lampart; Anna Rupińska; Zuzanna Jasińska; Kamila Krzewska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Duchenne muscular dystrophy (DMD) is a severe X-linked neuromuscular disorder characterized by progressive muscle degeneration due to mutations in the dystrophin gene. Current treatments primarily focus on symptom management. Delandistrogene moxeparvovec is a gene therapy designed to deliver a shortened, functional version of the dystrophin gene, potentially modifying disease progression. Aim of the study: To evaluate the clinical efficacy and safety of delandistrogene moxeparvovec in improving skeletal muscle function and physical performance in patients with DMD based on data from completed clinical trials. Methodology: The analysis includes four published clinical trials involving ambulatory boys aged 4–8 years with confirmed dystrophin mutations. Primary outcomes focused on changes in the North Star Ambulatory Assessment (NSAA), while secondary endpoints included time to rise from the floor and the 10-meter walk/run test. Study designs ranged from open-label to randomized, double-blind trials. Adverse events and regulatory outcomes were also considered. Conclusions: Delandistrogene moxeparvovec demonstrated variable improvements in motor function, with more pronounced benefits in younger age groups. Some trials showed statistically significant results, while others failed to meet primary endpoints. Adverse events, including serious complications, were reported. The therapy received FDA approval in 2023 and 2024 for defined patient subgroups, though some decisions were made despite inconclusive efficacy data.